Vaginal high dose rate brachytherapy alone in patients with intermediate- to high-risk stage I endometrial carcinoma after radical surgery. Issue 6 (1st October 2008) - Atahan, I. L.; Ozyar, E.; Yildiz, F.; Ozyigit, G.; Genc, M.; Ulger, S.; Usubutun, A.; KÖSE, F.; Yuce, K.; Ayhan, A.
Abstract : The objective of this study was to analyze the efficacy and morbidity of vaginal cuff brachytherapy alone in intermediate- to high-risk stage I endometrial cancer patients after complete surgical staging. Between October 1994 and November 2005, 128 patients with intermediate- to high-risk stage I endometrial adenocarcinoma were treated with high dose rate (HDR) brachytherapy alone after complete surgical staging. The intermediate- to high-risk group was defined as any stage I with grade 3 histology or stage IB grade 2 or any stage IC disease. The comprehensive surgery was in the form of total abdominal hysterectomy, bilateral salpingo-oophorectomy in addition to infracolic omentectomy, and routine pelvic and para-aortic lymphadenectomy. The median number of the lymph nodes dissected was 33. The median age at the time of diagnosis was 60 years. Forty patients were staged as IB (grade 2: 25 and grade 3: 15), and 88 patients were staged as IC (grade 1: 31, grade 2: 41, and grade 3: 16). A total dose of 27.5 Gy with HDR brachytherapy, prescribed at 0.5 cm, was delivered in five fractions in 5 consecutive days. Median follow-up was 48 months. Six (4.7%) patients developed either local recurrence ( n = 2) or distant metastases ( n = 4). Five-year overall survival and disease-free survival (DFS) rates are 96% and 93%, respectively. Only age was found to be significant prognostic factor for DFS. Patients younger than 60 years have significantly higher DFS ( P = 0.006). None of the patients experienced grade 3/4 complications due to the vaginal HDR brachytherapy. Vaginal cuff brachytherapy alone is an adequate treatment modality in stage I endometrial adenocarcinoma patients with intermediate- to high-risk features after complete surgical staging with low complication rates.